Subungual fibro‐osseous pseudotumour of the toe. (20th May 2015) - Meani, Rowena E; Bloom, Richard J; Battye, Shane; Chamberlain, Alex J
Abstract: Subungual fibro‐osseous pseudotumour of the toe is a rare osseous soft tissue tumour of which only six cases have been described in the literature. We present a case in a teenage boy that posed an instructive diagnostic challenge and discuss the distinguishing features of the various differential diagnoses. The subungual location is very rare. For such tumours, radiology is as vital as histopathology in making a diagnosis and excluding neoplasia. Accurate diagnosis requires careful clinico‐pathological and radiological correlation. These sorts of lesions may present to the dermatologist, not always the foot surgeon.